Livestock production in central Mali: Reproductive components in traditionally managed sheep and goats - Wilson, R.T.; Durkin, J.W. (Elsevier, 1988)
Presents results of a six year study conducted to determine the main reproductive parameters of traditionally managed sheep and goats in agro-pastoral systems near Niono-Mali.